1988
DOI: 10.1136/gut.29.9.1244
|View full text |Cite
|
Sign up to set email alerts
|

Acute ethanol dosage reduces the synthesis of smooth muscle contractile proteins in the small intestine of the rat.

Abstract: SUMMARY The effects of an acute dose of ethanol (75 mmol/kg body weight; ip) on protein synthesis were investigated in the small intestine of the rat (n=6). Control rats (n=6) were injected with isovolumetric 0.15 mol/l NaCI, ip. After 2 5 h, fractional rates of protein synthesis (defined as the percentage of tissue protein renewed each day by synthesis and RNA efficiencies (defined as the amount of protein synthesised per unit RNA) were measured with a large flooding dose (0.3 Ci/mol; 150 mmol/l; 150 [tmol/10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…There is evidence of wasting of lean body mass in alcoholic liver disease (ALD), especially of skeletal muscle [7], but little is known about the involvement of the gut in the wasting process. Studies in rats have provided evidence of depressed small-intestinal mucosal protein synthesis [8][9][10] in response to alcohol, suggesting the existence of similar deficits in humans. Furthermore, little is known about the functional correlates of possible gastrointestinal involvement in humans in response to chronic ethanol ingestion.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence of wasting of lean body mass in alcoholic liver disease (ALD), especially of skeletal muscle [7], but little is known about the involvement of the gut in the wasting process. Studies in rats have provided evidence of depressed small-intestinal mucosal protein synthesis [8][9][10] in response to alcohol, suggesting the existence of similar deficits in humans. Furthermore, little is known about the functional correlates of possible gastrointestinal involvement in humans in response to chronic ethanol ingestion.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis rates in subcellular protein fractions of intestinal smooth muscle in the entire regions of the gastrointestinal tract have never previously been investigated. The studies by Preedy et al (1988) and Preedy & Peters (1990) only investigated synthesis rates pertaining to protein subfractions of the entire small intestinal mass. Intestinal smooth muscle contractile protein synthesis has been measured by Millward et al (1980) in unspecified regions.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Preedy, Duane & Peters (1988) showed that intestinal contractile protein synthesis in vivo was relatively sensitive to acute ethanol dosage. Fractional synthesis rates of con-tractile proteins were reduced by 40-50% (p 辖 0.001), compared with an approximate 20% decline in the synthesis of mixed intestinal proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pellet was the 'stromal' protein fraction. 9 The terminology 'cytoplasmic' 'contractile' and 'stromal' was defined in detail in our previous paper.9 Briefly, the cytoplasmic fraction contains principally soluble enzyme proteins; the 'contractile' fraction contains proteins such as actin and myosin and other myofibrillar proteins; the 'stromal' fraction comprises of connective tissue proteins such as collagen, and possibly traces of unextractable contractile protein.…”
Section: Separation Of Protein Compartmentsmentioning
confidence: 99%